2019
DOI: 10.22564/rbgf.v37i4.2018
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the signatures of long-range persistence in seismic sequences along Circum-Pacific subduction zones

Abstract: In the present paper, we analyze the signatures of long-range persistence in seismic sequences along Circum-Pacific subduction zones, from Chile to Kermadec, extracted from the National Earthquake Information Center (NEIC) catalog. This region, known as the Pacific Ring of Fire, is the world's most active fault line, containing about 90% of the world's earthquakes. We used the classical rescaled range (R/S) analysis to estimate the long-term persistence signals derived from a scaling parameter called the Hurst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It is worth noting the universal character of the R/S method in the analysis of the behavior of fluctuations. A large number of studies in different areas of knowledge has shown that the so-called Hurst exponent extracted from within the MFDMA analysis provides a robust and powerful statistical method to characterize nonstationary fluctuations at different timescales [1,28].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…It is worth noting the universal character of the R/S method in the analysis of the behavior of fluctuations. A large number of studies in different areas of knowledge has shown that the so-called Hurst exponent extracted from within the MFDMA analysis provides a robust and powerful statistical method to characterize nonstationary fluctuations at different timescales [1,28].…”
mentioning
confidence: 99%
“…Working sample and data analysis. -Recently de Freitas et al [1] published a study about the fractal properties of a set of Circum-Pacific subduction zones distributed along the so-called Ring of Fire. As mentioned in the referred paper, these data were extracted from the National Earthquake Information Center (NEIC) catalog and they were selected from 12 regions of Flinn-Engdhal for applying our analysis as shown in table 1 [41].…”
mentioning
confidence: 99%
See 2 more Smart Citations